Benin : Joint Staff Advisory Note on the Poverty Reduction Strategy Paper; Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2008)
This Joint Staff Advisory Note reviews the latest Annual Progress Report (APR) on the implementation of the poverty reduction strategy (PRS) for Benin. The APR assesses progress in implementing the strategy during 2006 and the first half of 2007. The APR indicates that significant progress has been made in strengthening the macroeconomic framework. The APR highlights some improvement in social indicators but indicates that, at the current pace, Benin would not be able to reach all the Millennium Development Goal targets by 2015.